Evaluation Of The Sustainability Of Community Empowerment Of The National Literacy Movement: A Study Of The Literacy Village Program - Mutakin, Jaenal; Shantini, Yanti; Kamarubiani , Nike (Sean Institute, 2024)
The level of literacy in our culture, particularly among students and the broader population, remains significantly deficient. Out of the 250 million people living in Indonesia, the literacy rate does not match that figure. The Indonesian people, as a whole, lacks critical thinking skills, as seen by their frequent acceptance of and belief in false news and unsubstantiated claims. In 2015, the government, namely the Ministry of Education and Culture, advocated for the establishment of literacy village programs and services. This strategic measure is seen very suitable in response to diverse national and international policies, as well as in alignment with a worldwide educational movement aimed at eliminating ignorance and prejudice, one manifestation of which is evident in public discretion. The creation of this literary hamlet is a strategic measure aimed at safeguarding society against the ignorance and scarcity of knowledge. May this literary village operate efficiently and provide significant advantages to the surrounding community. Village Literation, a strategic policy in public education that has been implemented for five years, is a fascinating subject to study and analyze. Its impact on education and training programs, social and cultural life, and community development is particularly noteworthy. This study employs a qualitative descriptive methodology. This research reveals that despite being located in areas with limited resources, the village literacy program has been successful in offering innovative educational services. It has significantly improved the dignity of citizens and empowered the community through the mastery of six fundamental literacies: reading, numeracy, science, digital skills, financial literacy, as well as cultural and citizenship education. Data collecting operations were conducted to investigate the implementation of several literacy village programs and services in many locations, including Tegal District, Kendal District, Sleman District, Bogor District, and Kuningan District.